Decadal variations of blocking and storm tracks in centennial reanalyses. Issue 1 (1st January 2019) - Rohrer, Marco; Brönnimann, Stefan; Martius, Olivia; Raible, Christoph C.; Wild, Martin
Abstract: Extreme weather events in the mid-latitudes are often associated with weather systems, such as extratropical cyclones or blocks. However little is known about the decadal variation in the frequency of blocks and the activity of storm tracks and their relation to the two most important low-frequency oceanic modes of variability, the Atlantic multidecadal oscillation (AMO) and the Pacific decadal oscillation (PDO). To address this question, first the representation of blocks, storm tracks and Alpine circulation types is assessed in recently released centennial reanalyses during the 20th century. While interannual variability is represented similarly in all centennial reanalyses, the trends in particular for storm track activity before 1950 differ substantially between the NOAA 20th century reanalyses (20CR and 20CRv2c) and ECMWF centennial reanalyses (ERA-20C and CERA-20C). Therefore, the analysis of the connection between the AMO and PDO and the mid-latitudinal circulation is restricted to the period 1950–2010. All centennial reanalyses agree on the anomaly patterns associated with the different AMO/PDO phases. We find no significant connections except a southward (northward) shift of the storm track over the North Pacific as well as the North Atlantic during the positive (negative) PDO phase. The ERA-20CM atmosphere-only model ensemble captures this relationship, indicating that the ocean forces the atmosphere in the North Pacific. For studies investigating periods earlier than 1950, we recommend using several reanalysis products to ensure the robustness of results.